2012
DOI: 10.2460/ajvr.73.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gel column, card, and cartridge techniques for dog erythrocyte antigen 1.1 blood typing

Abstract: Objective To compare accuracy and ease of use of a card agglutination assay, an immunochromatographic cartridge method, and a gel-based method for canine blood typing. Sample Blood samples from 52 healthy blood donor dogs, 10 dogs with immune-mediated hemolytic anemia (IMHA), and 29 dogs with other diseases. Procedures Blood samples were tested in accordance with manufacturer guidelines. Samples with low PCVs were created by the addition of autologous plasma to separately assess the effects of anemia on te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(117 citation statements)
references
References 11 publications
5
110
2
Order By: Relevance
“…We did not assess the monoclonal anti‐DEA 1 antibodies from Kansas State University that are used in the DEA 1.1 typing cards 2. However, weak and strong typing reactions have also been observed with that typing kit 13, 19…”
Section: Discussionmentioning
confidence: 99%
“…We did not assess the monoclonal anti‐DEA 1 antibodies from Kansas State University that are used in the DEA 1.1 typing cards 2. However, weak and strong typing reactions have also been observed with that typing kit 13, 19…”
Section: Discussionmentioning
confidence: 99%
“…This test is sensitive for the detection of DEA 1 and is suited for screening blood donors in a blood bank program [19, 20]. This study used, for only the third time in the canine blood typing, column gel agglutination with polyclonal antibodies for DEA 4 and DEA 7 [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…DEA 1 status was determined using a commercially available card agglutination technique (RapidVet-H, Canine DEA 1.1, Agrolabo SpA, Scarmagno, Turin, Italy) according to the manufacturer's instructions and as previously described [19, 20]. The principle of this card-based agglutination test is a visible hemagglutination reaction resulting from the binding of the DEA 1 RBC surface antigen to a murine monoclonal antibody that is lyophilized on the card test.…”
Section: Methodsmentioning
confidence: 99%
“…A limitation of this study was that only one blood typing method was used, however, there is no currently accepted gold standard for canine blood typing (Giger and others 2005) and previous studies have demonstrated that the cartridge kit (Quick Test DEA 1.1, Alvedia, Lyon, France) is accurate (Seth and others 2012, Blois and others 2013) and performs well so long as dogs have haematocrit >40 and do not have immune mediated haemolytic anaemia (Seth and others 2012, Blois and others 2013). Another limitation of this study was that extensive blood typing for multiple DEAs was not performed, however, the blood type of the ideal canine blood donor is not uniformly agreed on among transfusion experts (Hale 1995, Andrews 2006, Tocci and Ewing 2009, Kessler and others 2010).…”
Section: Discussionmentioning
confidence: 99%